Money and inflation: Lessons from the US for ECB monetary policy - Ansgar Belke; Thorsten Polleit (Research On Money in the Economy (ROME), 2007)
We turn our attention to the role of money for determining nominal magnitudes. Using US data, we find that the aggregate 'nominal output plus and stock market capitalisation' is closely related to the money stock, lending support to one of Milton Friedman's key monetarist propositions. This finding should be particularly important for ECB monetary policy: an inflation-free euro plays a crucial role for European economic and political integration. We conclude that monetary policy must keep a very close eye on money supply if it wants to prevent consumer and/or asset price inflation.
Keywords: C22; E52; G12; 330; Money; asset price inflation; monetary policy